Development of an AI-Based Platform to Customize Learning Experiences in Religious Education: Papuan Youth Emik Characterized by Local Wisdom - Erly Lumban Gaol; Francisco Noerjanto; Agustinus Kia Wolomasi; Donatus Wea (Journal of Social Science Utilizing Technology, 2024)
Background. Religious education plays a crucial role in shaping moral and cultural values, especially in diverse regions like Papua, Indonesia. Traditional methods of religious education may not adequately address the unique needs of Papuan youth, who are deeply rooted in local wisdom and cultural values. The development of an AI-based platform offers an innovative solution to personalize and enhance learning experiences, ensuring that religious teachings are relevant and engaging for this demographic. Purpose. This study aims to design and develop an AI-based platform that customizes learning experiences for Papuan youth, integrating religious education with local wisdom and cultural values. The platform seeks to improve learning engagement, foster a deeper understanding of religious teachings, and preserve cultural identity. Method. The research employed a design-based research methodology, combining AI algorithms, educational content analysis, and participatory design involving local educators and community leaders. The platform was tested with a sample group of Papuan youth to evaluate its effectiveness in personalizing learning experiences. Results. The AI-based platform demonstrated a significant increase in student engagement, with personalized content tailored to local customs and religious values. Feedback from participants indicated a strong connection between the learning material and their cultural identity. Conclusion. The AI-based platform is an effective tool for customizing religious education for Papuan youth, blending modern technology with traditional wisdom. This approach promotes a more engaging, culturally relevant, and personalized learning experience.